Dentinogenesis and Tooth-Alveolar Bone Complex Defects in BMP9/GDF2 Knockout Mice - Huang, Xia (Stem Cells Dev, 2019)
Tooth development is regulated by sequential and reciprocal epithelium-mesenchymal interactions and their related molecular signaling pathways, such as bone morphogenetic proteins (BMPs). Among the 14 types of BMPs, BMP9 (also known as growth differentiation factor 2) is one of the most potent BMPs to induce osteogenic differentiation of mesenchymal stem cells. The purpose of this study was to examine potential roles of BMP9 signaling in tooth development. First, we detected the expression pattern of BMP9 in tooth germ during postnatal tooth development, and we found that BMP9 was widely expressed in odontoblasts, ameloblasts, dental pulp cells, and osteoblasts in alveolar bones. Then, we established a BMP9-KO mouse model. Gross morphological examination revealed that the tooth cusps of BMP9-KO mice were significantly abraded with shorter roots. Micro-computed tomography and three-dimensional reconstruction analysis indicated that the first molars of the BMP9-KO mice exhibited a reduced thickness dentin, enlarged pulp canals, and shortened roots, resembling the phenotypes of the common hereditary dental disease dentinogenesis imperfecta. Further, the alveolar bone of the BMP9-KO mutants was found to be shorter and had a decreased mineral density and trabecular thickness and bone volume fraction compared with that of the wild-type control. Mechanistically, we demonstrated that both dentin sialophosphoprotein and dentin matrix protein 1 were induced in dental stem cells by BMP9, whereas their expression was reduced when BMP9 was silenced. Further studies are required to determine whether loss of or decreased BMP9 expression is clinically associated with dentinogenesis imperfecta. Collectively, our results strongly suggest that BMP9 may play an important role in regulating dentinogenesis and tooth development. Further research is recommended into the therapeutic uses of BMP9 to regenerate traumatized and diseased tissues and for the bioengineering of replacement teeth.